H HUBUNGAN PENGETAHUAN TERHADAP PENERAPAN POLA ASUH ORANG TUA PADA ANAK BERKEBUTUHAN KHUSUS STUDI LITERATUR - Aan Devianto (Journal of Nursing Invention, 2022)
Background: Children with special needs are children who have differences with children in general. Children with special needs are defined as individuals who have different characteristics from other individuals or are considered abnormal by society in general. Objective:Explaining knowledge with parenting patterns for Children with special needs based on a critical study of the journal. Method:This research is a literature study using 6 articles that have been published through the search engines of Google Schoolar, EBSCO, and Garuda Portal by selecting as many as 19,239 articleswith the keywords of knowledge and parenting patterns of children with special needs. The search is limited to 2016-2020 which can be accessed for free full text. The article is then subjected to a process of identification, screening, eligibility, and article inclusion. Result:Adequate knowledge will have an impact on the mother's skills in providing good and correct parenting so that children with special needs can still grow and develop in the midst of the limitations they experience, and from 6 articles in this study it was found that there was a relationship between knowledge and parenting styles of mothers in dealing with the child with special needed. Conclusion: There is a significant relationship between knowledge and parenting styles of mothers in dealing with children with special needs.